The Dynamism of Poems in Pisarani and Their Impact on The Sentiments of Kurdish Poetry - عبدالله سعید محمد (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The current research is entitled “The Dynamism of poems in Pisarani and their impact on the sentiments of Kurdish poetry”. Generally speaking, a poem emerges out of the political, sociological, and the intellectual context of the poet. As we touched upon it that each poem has its own conditions and its own political and social influences in which the poet lives and in which he weaves his literary creativity. Classical Kurdish poetry is a part of the Kurdish culture; it has always been a genuine tool to raise individuals’ awareness. the poet’s language delves into the magical realms of the linguistic signs of the poem, so the poet Pisarani was able to draw unilaterally a linguistic mosaic in the mind of the reader. Hawrami poetry is considered the essence of the rhythmic authenticity of the language because the term (Abruism), means love and conscience which are enough to make it a song and sing the Kurdish sentimental poetry, in addition to that the Hawraman poem consists of sound and rhythm and the sounds, rhythm and morphology move between them to generate a new poem charged with poetic connotations to reach inside souls that feel alienated. The Horanmanic poem is distinguished by its innate and rare rhetoric of rare taste and full of poetic values. In addition, it is full with the framework of a sophisticated style with mystical and simple rhetorical contents that rise to the level of poetic discourse.